Enhancing cross-border disaster management in the Balkans, a framework for collaboration part I - Despoina Kanteler; Ioannis Bakouros (Journal of Innovation and Entrepreneurship, 2024)
This abstract presents the methodological approach employed in a comprehensive study focusing on decision making in a collaborative manner in disaster management, with a specific emphasis on cross-border disasters in the Balkan region. Disasters, characterized by their sudden and profound impacts on human life, property, and the environment, necessitate a well-coordinated response. Emergency management, which encompasses preparation, response, and recovery phases, relies on the collective efforts of diverse agencies, organizations, and individuals to ensure an efficient response. The preparedness phase is particularly vital, entailing the formulation and execution of plans, policies, and procedures to effectively respond to disasters. Cross-border disasters, which transcend international borders and affect multiple countries and communities, present unique challenges due to the need for coordination and cooperation among various national governments and organizations. This research addresses the multifaceted aspects of disaster preparedness and cross-border disaster management within the intricate context of the Balkan region. The management of disasters demands a coordinated and proactive approach, especially when dealing with cross-border disasters. International cooperation and effective communication are essential for an effective response and minimizing the disaster's impact on affected communities. Consequently, it is imperative to establish collaborative frameworks that enhance cross-border disaster risk reduction on various levels. To construct the components of a cross-border emergency preparedness framework, an extensive literature review was conducted, identifying ten essential pillars for disaster management. Subsequently, 129 recommendations formed the initial framework, which became the subject of a Delphi study. In this study, 104 experts from 12 participating Balkan countries aimed to reach a consensus on the framework's elements. The study unveiled common aspects necessary for a cross-border preparedness framework tailored to the Balkans' geographical characteristics. This framework was jointly endorsed by various emergency management experts with distinct functions and roles in disaster response. The process and results of this thesis underscore the critical need among Balkan countries to establish a tangible and sustained collaborative environment. This environment should foster a shared mindset and create a pathway towards resilient and sustainable cross-border emergency management cooperation and unity among Balkan countries.
Keywords: 650; Cross-border emergency management; Decision-making; Delphi study; Regional development